Potential of stingless bee honey in modulating skin ageing of human dermal fibroblast cells - Malik, Nurfairuz Abdul (2021)
Skin is the visible indicator of ageing. During ageing, the excessive production of reactive oxygen species (ROS) contributes to the increasing of matrix metalloproteinase (MMP) production that causes collagen degradation. Increasing formation of ROS can be prevented by antioxidants such as stingless bee honey. Stingless bee honey is a good source of natural antioxidants that might delay skin ageing. Therefore, this study aims to elucidate the potential roles of stingless bee honey on the modulation of skin ageing in human dermal fibroblast cells. The optimum concentration and incubation time of stingless bee honey were determined using MTS assay, while lipid peroxidation analysis was quantitated using flow cytometer. Gene expression of matrix metalloproteinase 1 (MMP-1) and collagen type I (COL1A1) were analysed using real time RT-PCR. Results showed that the concentration of stingless bee honey at 0.02% for 72 hours incubation significantly increased the viability of human dermal fibroblast cells compared to untreated cells. Treatment with 0.02% of stingless bee honey for 72 hours also showed significant upregulation of COL1A1 expression in senescent human dermal fibroblast cells and downregulation of MMP-1 expression in both pre-senescent and senescent human dermal fibroblast cells. However, no significant changes were observed on lipid peroxidation analysis in both pre-senescent and senescent human dermal fibroblast cells when treated with stingless bee honey. In conclusion, this study suggested that stingless bee honey beneficially delayed skin ageing through downregulation of MMP-1 expression and potentially promotes collagen synthesis through upregulation of COL1A1 expression in human dermal fibroblast cells.